The Application of Chicken Manure and NPK Fertilizer on Growth and Yield of Shallot Plant in Tidal Land of Banyuasin Regency - Susilawati Susilawati; Irmawati Irmawati; Sri Sukarmi; Muhammad Ammar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The aim of the study was to obtain proper technique for cultivating shallots of Bima Brebes variety through the use of chicken manure and NPK fertilizer on tidal land. The research was located on tidal land in Sukatani Village, Tanjung Lago District, Banyuasin Regency, South Sumatra Province, located at a position of 1.30° – 4.0° South Latitude and 104° 00' – 105° 35' East Longitude. The study used a randomized block design with one treatment factor and three replicates. The treatment was the dose of organic chicken manure with 5 levels, namely P0 = no chicken manure; P1 = 10 tons of manure per hectare; P2 = 15 tons of manure per hectare; P3 = 20 tons of manure per hectare; P4 = 25 tons of manure manure per hectare. Each treatment was mixed with NPK fertilizer at a dose of 200 kg NPK ha-1 (M). Data analysis was carried out by analysis of variance using F test and least significance difference (LSD) test. The variables observed were leaf length, leaf number, plant dry weight, specific leaf area, specific leaf weight, root-shoot ratio, relative growth rate, net assimilation rate, bulb fresh weight, bulb number, bulb diameter, bulb dry weight, and percentage of bulb shrinkage. The results showed that the use of chicken manure 10 tons/ha and 200 kg NPK/ha affected the growth of shallots on leaf length, root-shoot ratio, relative growth rate, bulb fresh weight and bulb dry weight. It was then concluded that it can increase the growth and yield of shallots of Bima Brebes variety on tidal land.